Study of etiological profile, risk factors and immediate outcome of neonatal sepsis - Shah, Nidhi S.; Srivastava, Ritika; Mehta, Tanvi; Shah, Ashka; Chandwani, Chandni (International Journal of Contemporary Pediatrics, 2025)
Background: In India, Gram negative bacteria such as CONS, Klebsiella spp, Acinetobacter spp and E. coli are the main pathogen. Due to the variation in prevalence of associated microorganism and resistant pattern, regional hospital based prospective study should be carried out to know the microorganism pattern of neonatal sepsis. Aim is to study the demographic profile of neonates with sepsis, to study maternal and neonatal risk factors for sepsis, to study pattern of causative microorganism. Methods: The study was carried out among 226 neonates admitted in NICU at Dhiraj hospital and having sepsis. Patient’s information was collected as per the prescribed proforma. Antibiotic sensitivity tests (AST) were performed for all isolates recovered from infant cultures. Data was analysed with Epi info version 7.1. Results: The ratio of extramural to intramural for neonatal sepsis was higher (1.9:1). Anaemia, leaking per vaginum, fetal distress, unable to cry immediate after birth, previous hospitalization were most common risk factors. Coagulase Negative Staphylococci, S. aureus, Acinetobacter Baummanni, Klebsiella pneumonia were commonly isolated organism. Gram positive pathogens were sensitive to vancomycin, tetracycline and gram-negative pathogens were sensitive to tigecycline and colistin. Conclusion: Gram negative organism sepsis is still prevalent than gram positive sepsis but without major difference. The common pathogens exhibit a high degree of resistance to ampicillin, gentamicin, and third generation cephalosporins. However, most were susceptible to Vancomycin, Tetracycline, Tigecycline, Teicoplanin, and Doxycycline.